"Who Are These People and Why Are They Saying These Things?": George Heller and the Growth of Historical Research in Music Education. Issue 1 (October 2020) - Grady, Melissa L.
This historical investigation explores the life of George N. Heller (1941–2004) and his influence on historical research in music education and music therapy. By means of primary source materials, including preserved presentation resources and outlines, publications, and interviews, this historical investigation explores Heller's life and career and the influences that informed his work. This study argues that at a time when quantitative methods dominated music research journals, George Heller's efforts coincided with the progress and acceptance of historical research in music education and music therapy. Through his historical research publications, his encouragement of student research, his mentoring of colleagues, and his position as founding editor of the Bulletin of Historical Research in Music Education, George Heller championed historical research at a critical juncture in music education scholarship.